We want to use the Addition-Subtraction method to solve
8.92x - 5.42y = 3.41 (1)
5.83x + 1.07y = 2.37 (2)
We shall eliminate y from the two equations by Addition.
Multiply (1) by 1.07 and multiply (2) by 5.42 to obtain
1.07*(8.92x - 5.42y) = 1.07*3.41
9.5444x - 5.7994y = 3.6487 (3)
5.42*(5.83x + 1.07y) = 5.42*2.37
31.5986x + 5.7994y = 12.8454 (4)
Add (3) and (4) to obtain
9.5444x - 5.7994y + 31.5986x + 5.7944y = 3.6487 + 12.8454
41.143x = 16.4941
x = 0.4009
From (2), obtain
1.07y = 2.37 - 5.83x
= 2.37 - 5.83*0.4009
= 0.0328
y = 0.0307
Answer:
x = 0.4009
y = 0.0307